The fire-sale channels of universal banks in the European sovereign debt crisis - Giulio Bagattini; Falko Fecht; Patrick Weber (Deutsche Bundesbank, 2019)
We use a unique security-level data set to analyze correlations in bond trading of banks, their respective retail customers and their affiliated mutual funds. Matching banks' proprietary holdings with the holdings of their funds and their retail customers for the period 2009-2016 at the security level, we find evidence that banks sold off risky euro-area sovereign bonds to both their retail customers and their affiliated mutual funds (particularly their public funds) during the European sovereign debt crisis. Overall, this enabled banks with affiliated mutual funds to sell off larger amounts of their risky sovereign bond holdings, while bank-affiliated mutual funds acquired more risky sovereign bonds compared to their unaffiliated peers. The larger the risky sovereign bond position a fund acquired from its parent bank, the lower are the fund's short-term raw returns controlling for the risky bonds the fund overall acquired. Our findings show that banks use their customers portfolio and their affiliated funds as liquidity provider when they sell off their risk bonds without paying the funds the adequate liquidity premium. On the one hand, this points to a severe conflict of interest between banks' own account trading and their asset and wealth management services. On the other hand, it highlights that the severity of fire-sale contagion depends on the organizational structure of the financial sector.
Keywords: G01; G21; G23; 330; fire sales; sovereign bonds; own account trading; bankaffiliated mutual funds; conflict of interest